“When one has no REAL illness”—analysis of the knowledge component of mental health literacy in children and adolescents of parents with a mental illness - Kinzenbach, Lina; Praum, Katharina; Stracke, Markus; Schwenck, Christina; Kieser, Meinhard; Otto, Kathleen; Reck, Corinna; Steinmayr, Ricarda; Wirthwein, Linda; Zietlow, Anna-Lena; Christiansen, Hanna; , the COMPARE-family Research Group (Frontiers in Psychiatry, 2024)
Introduction and objective Mental Health Literacy (MHL) is important in promoting youth mental health. One key aspect of MHL is knowledge about mental disorders, which is particularly relevant for populations at risk for developing mental disorders, such as children of parents with a mental illness (COPMI), representing a mechanism within the transgenerational transmission. Currently, COPMI’s level of disorder knowledge in general, and about the specific parental disorder has not been comprehensively researched. We, therefore, aimed to assess COPMI’s disorder knowledge and clarify its association with COPMI’s age and sex exploratively. To assess both general and disorder-specific knowledge, we took a novel approach that makes disorder knowledge comparable across samples and over time. Methods A mixed method analysis of N = 181 semi-structured MHL interviews with COPMI (aged 5 to 17 years) was carried out in the COMPARE—family study in Germany. We conducted a DSM-oriented deductive qualitative content analysis to assess COPMI’s general and specific disorder knowledge. Chi-square tests served to identify age and sex differences. Results Children revealed limited knowledge of mental disorders in general, whereas adolescents displayed more knowledge that was also partly consistent with descriptions of classification systems like the DSM-5. The level of specific knowledge about the parent’s disorder depended on the disorder group. More children displayed adequate knowledge of somatic and anxiety disorders compared to trauma and depressive disorders, and more adolescents displayed adequate knowledge of depressive and anxiety disorders. COPMI’s age and sex were found to be significantly associated with disorder knowledge: adolescents exhibited higher levels of adequate general and specific disorder knowledge, and males exhibited higher levels of adequate general disorder knowledge. Conclusion Assessing COPMI’s disorder knowledge and identifying associated age and sex differences yield valuable insights into the knowledge component of the MHL theory. Our findings can help to improve psychoeducational interventions for COPMI by orienting them to their prevailing levels of disorder knowledge. We recommend employing and extending the DSM-oriented deductive approach to assess knowledge within MHL. Analyses involving additional assessments within the COMPARE—family study are in preparation to identify potential knowledge gains over time, and associations to COPMI’s own well-being and mental health symptoms.